Performance analysis and optimization of permanent magnet flux switched linear motor for ropeless elevator - Xu, Xiaozhuo; Zhang, Wei; Feng, Haichao; Zhao, Yunji; Ai, Liwang (IET electric power applications, 2023)
Permanent magnet linear synchronous motor (PMLSM) is one of the ideal driving sources of ropeless elevators. However, such motors, whether moving magnetic or moving coil, will produce the problem of excessive cost under long travel. The permanent magnet flux switched linear motor (PMFSLM) with permanent magnets (PMs) and copper coils on the mover side greatly reduces the cost. A U‐type PMFSLM is proposed in the paper. First, a PMFSLM is proposed and investigated, quantitatively comparing with PMLSM for the ropeless elevator system. Second, aiming at the problem of flux leakage at the top of PMFSLM, a U‐type PM (UPM) structure is presented. The electromagnetic performance of PMFSLM and UPM‐FSLM have been compared and summarised. The comparison results show that UPM‐FSLM solves the defect of top flux leakage, increases thrust by 4.34%, reduces thrust ripple by 28.10%, and has better electromagnetic performance than PMFSLM. Afterwards, the elevator passenger capacity of PMFSLM and UPM‐FSLM are simulated and calculated and the feasibility is analysed. Finally, a prototype of PMFSLM has been built and measured.